2017
DOI: 10.2351/1.4983667
|View full text |Cite
|
Sign up to set email alerts
|

Turbine blade tip single crystalline clad deposition with applied remelting passes for well oriented volume extension

Abstract: The objective of this work was to achieve a single crystalline (SX) clad on the tip of an SX turbine blade. It was assumed that remelting could extend the SX-height by resolidifying the misoriented volume of its clad tracks. Thus, remelting was used as a tool to ease the clad epitaxy. All tests were performed with SX Ni-based superalloys CMSX-4 or PWA 1426. To determine the remelting parameters, the following methodology was devised: An ideal energy input per unit was determined for each clad track shape by ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In previous works developed by the LMP-Laser group, consistent results are reported: Pôrto et al ( 2019) performed a methodology for parameterizing the remelting process of single beads deposited via LMD and observed that throughout the evaluated parameter window, especially those deposited with higher energy, resulted in complete single bead remelting. Pereira et al (2017), in the remelting evaluation applied in the misorietated volume reduction for turbine blades, they highlight similar behavior, as well as in the work, of similar objective, presented by Rottwinkel et al (2017). Cao and Gu (2015), when evaluating density ratio, microstructures, and performance of TiC / Inconel 625 nanocomposites deposited via LMD, they observed that when increasing the energy, operating temperature is high enough to increase melt pool temperature and reduce the liquid viscosity, improving wettability.…”
Section: Microhardness Test and Pin-on-disk Tribological Test In Dry Mediummentioning
confidence: 76%
See 1 more Smart Citation
“…In previous works developed by the LMP-Laser group, consistent results are reported: Pôrto et al ( 2019) performed a methodology for parameterizing the remelting process of single beads deposited via LMD and observed that throughout the evaluated parameter window, especially those deposited with higher energy, resulted in complete single bead remelting. Pereira et al (2017), in the remelting evaluation applied in the misorietated volume reduction for turbine blades, they highlight similar behavior, as well as in the work, of similar objective, presented by Rottwinkel et al (2017). Cao and Gu (2015), when evaluating density ratio, microstructures, and performance of TiC / Inconel 625 nanocomposites deposited via LMD, they observed that when increasing the energy, operating temperature is high enough to increase melt pool temperature and reduce the liquid viscosity, improving wettability.…”
Section: Microhardness Test and Pin-on-disk Tribological Test In Dry Mediummentioning
confidence: 76%
“…The coatings showed good surface quality concerning the layer continuity and irregularities absence (such as waviness and depressions). The remelted surface aspect was even better compared to the as-deposited surface since the first did not exhibit unmelted powder particles and showed a lower waviness level (see topic 2.1., paragraph 2) compared to the latter (Rottwinkel et al, 2017;Pôrto et al, 2019). Besides that, none of the coating samples (both as-deposited and remelted) did not show material detachments during the tribological test performed (results of which will be presented and discussed in topics 3.2. and 3.3.).…”
Section: Surface Aspects and Coatings Microhardnessmentioning
confidence: 91%
“…A laser cladding technique was applied to coat nickel-based composite on H13 steel, which offers enhanced wear resistance and thermal fatigue properties [ 35 ]. Although laser clad deposits produced superior properties, the small spot or concentration size of lasers hinders large widths to be deposited in a single pass [ 36 ]. Magnetron sputtered molybdenum di-sulfide titanium nitride coatings on high-speed steels produced superior surface hardness [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CW LPD process shows a potential to effectively restore worn SX components. [7][8][9][10] During the rapid solidification of the CW LPD process of SX superalloy, a high-energy laser beam continuously melts the SX base and injected metallic powders, forming a fast-moving molten pool. Fine columnar dendrites grow epitaxially with crystallographic orientation identical to the SX base.…”
Section: Introductionmentioning
confidence: 99%